PEMIKIRAN SEORANG PRAKTISI DIPLOMASI: MERETAS PEMAHAMAN PRAKSIS TERKAIT PERKEMBANGAN DIPLOMASI DI ABAD 21 - H.E Ramli Saud (Universitas Nasional, 2016)
Discussion on the relation between diplomacy and International Relations enriches discourse about the linkages between diplomacy as a practical activity and International Relations theory today. This paper will elevate the discourse about diplomacy as an institution in InternationalRelations (IR) from the practitioner’s vantage point. Verily diplomats and mainstream IR theory have been mutually estranged; Diplomats often find international relations (IR) books strange; they often bewildered when they read–or more likely reread the contemporary theory of IR or myriad concepts of IR such as “life cycle of norms”. This paper argued that IR theory has failed to acknowledge the logic of practice in diplomacy and it does not capture the bodily experience to being a diplomat. Departing from above mentioned context this paper want to provide a richer view of how diplomacy works in practice, by showing that diplomacy is much more than the mediation of estrangement. This paper will also potray the actual development of diplomatic practice in order to strengthen the understanding of diplomacy in the context of international relations today. Of course, the primary aim of this paper is to provide a proper comprehension on diplomacy and to juxtapose the relevance between diplomacy on the level of praxis and IR Theory as an academic dissemination.